Determinants of quality of life of cancer patients at a tertiary care medical city in Riyadh, Saudi Arabia - AlJaffar, Mohammed A.; Enani, Sari S.; Almadani, Ahmad H.; Albuqami, Fay H.; Alsaleh, Khalid A.; Alosaimi, Fahad D. (Frontiers in Psychiatry, 2023)
Introduction: Cancer is a major public health concern in Saudi Arabia, as incidences are increasing at ‎an unprecedented rate. Moreover, cancer survivors have to cope with psychological, physical, social, ‎and economic challenges, all of which can impact quality of life (QoL).‎ Objectives: This study aims to explore the sociodemographic, psychological, clinical, cultural, and ‎personal factors that could affect the overall QoL of cancer patients. Methods: A total of 276 patients who attended the oncology outpatient clinics between January ‎‎2018 to December 2019 were included. Participants included cancer ‎patients in a tertiary center in Riyadh, the King Saud University Medical City.‎ QoL was assessed with the Arabic version of the European ‎Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30. Psychosocial ‎factors were assessed with a number of validated scales. ‎ Results: QoL was poorer among patients who were female (p = 0.001), have visited a psychiatrist (p ‎‎= 0.028); were taking psychiatric medications (p = 0.022); and had experienced anxiety (p < 0.001), ‎depression (p < 0.001), and distress (p < 0.001). The most used method to self-treat was Islamic ‎Ruqya (Spiritual Healing) (48.6%), and the most often perceived cause for developing cancer was evil ‎eye or magic (28.6%). Good QoL outcomes were associated with biological treatment (p = 0.034) and ‎satisfaction with health care (p = 0.001). A regression analysis showed that female sex, depression, ‎and dissatisfaction with health care were independently associated with poor QoL Conclusion: This study demonstrates that several factors could influence the QoL of cancer patients. ‎For instance, female sex, depression, and dissatisfaction with health care were all predictors of poor ‎QoL. Our findings support the need for more programs and interventions to improve the social services for cancer patients, along with the need to explore the social difficulties oncology patients face and address such obstacles through improving social services by expanding the scope of social workers’ contribution. Larger multi-center longitudinal studies are warranted to examine the generalizability of the ‎results.‎